Diagnosis and management of a patient with recurrent variant angina and history of percutaneous coronary intervention: vasospasm and percutaneous coronary intervention. Issue 1 (January 2018) - Fineschi, Massimo; D'Ascenzi, Flavio; Sirbu, Vasile; Mondillo, Sergio; Pierli, Carlo
Abstract : Supplemental Digital Content is available in the text